"I Know That I Do Not Know": Nicholas of Cusa’s Augustine - Dubbelman, Samuel J. ca. 20./21. Jh. (Harvard theological review, 2020)
Nicholas of Cusa read Augustine, like he read Dionysius the Areopagite, as teaching that God was best known and encountered in an understanding of one’s own ignorance of ultimate reality (learned ignorance). Cusa’s use of Augustine in Defense of Learned Ignorance, On the Vision of God, and On the Not-Other helps recover the importance of learned ignorance in Augustine’s own writings. This study tracks learned ignorance as an essential mechanism of Augustine’s pursuit of wisdom through his early writings, the Confessions, and the later anti-Pelagian treatises. Learned ignorance functioned as philosophical dialectic in his earliest treatises, a practice of prayer in the Confessions, and as both polemic and apophatic theodicy in his later writings. Augustine’s shifting conceptualization of learned ignorance, in turn, helps recover how Cusa often preached learned ignorance as the humility of faith. Thus, Cusa’s commitment to learned ignorance derived from both the Neoplatonic dilemma of knowing the unknowable and the Augustinian understanding of original sin as pride and redemption as humility.